Gallium nitride-based red light emitting diode epitaxial structure and preparation and application thereof

By growing the composite protective layer in InGaN-based red LED, the compressive stress and thermal annealing damage of the quantum well are reduced, and the internal quantum efficiency of the red LED is significantly improved, solving the problem of low quantum efficiency in the prior art.

CN119403316APending Publication Date: 2025-02-07DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498972.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The quantum efficiency of existing InGaN-based red LEDs is very low, especially under the conditions of reduced chip size and high In-component conditions, the efficiency attenuation is severe and it is difficult to meet application requirements.

Method used

Between the high-indium (In) component red light active region and the high-temperature p-type layer, a composite protective layer with stress release effect is grown, which reduces the compressive stress of the red light quantum well and reduces the high-temperature p-type layer to the quantum well. thermal annealing damage.

Benefits of technology

By using a composite protective layer, the internal quantum efficiency of the gallium nitride-based red light-emitting diode is significantly improved, up to 110%, solving the problem of low quantum efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403316A_ABST
    Figure CN119403316A_ABST
Patent Text Reader

Abstract

The invention discloses a gallium nitride-based red light emitting diode epitaxial structure and preparation and application thereof. The epitaxial structure sequentially comprises a sapphire substrate, a low-temperature GaN nucleating layer, a high-temperature non-doped GaN buffer layer, an n-type GaN layer, a low-temperature GaN V-type layer, an In < x > < 1 > Ga < 1-x > < 1 > N / GaN stress release layer, an In < x > Ga < 1-x > N / In < y > Ga < 1-y > N multi-quantum well light-emitting layer structure MQW, a composite protection layer, a p-type Al < y > < 1 > Ga-y < 1 > N electron barrier layer, a high-temperature p-type GaN layer and a p-type InGaN contact layer from bottom to top. The problem that the quantum efficiency of an existing InGaN-based red light LED is very low is solved. According to the invention, a composite protection layer with a stress release effect is grown between a high indium (In) component red light active region and a high-temperature p-type layer. Compared with an LED sample without a composite protection layer, the internal quantum efficiency is remarkably improved, and the maximum internal quantum efficiency is up to 110%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor optoelectronic technology, and in particular to a gallium nitride-based red light emitting diode epitaxial structure and its preparation and application. Background Art

[0002] In the field of full-color LED displays, red, green, and blue primary color light sources are required. Currently, red LEDs are typically based on the second-generation semiconductor AlInGaP material system. Blue and green LEDs are based on the third-generation semiconductor AlInGaN material system. Multiple studies have shown that the external quantum efficiency and other performance characteristics of red LEDs based on phosphide structures degrade as chip size decreases. When chip size is reduced to the micrometer scale, performance degradation becomes even more severe due to the long carrier diffusion length and high density of surface defects on the sidewalls, with efficiency plummeting to below 1%. Furthermore, the disadvantages of the second-generation semiconductor AlGaInP material system are evident in the mass transfer process of Micro LED chips. Mass transfer requires excellent mechanical strength to prevent cracking during chip handling and placement. The poor mechanical properties of AlGaInP material add new challenges to mass transfer. From an environmental perspective, the P source used in the growth of AlGaInP is highly toxic, making it unsuitable for sustainable development strategies.

[0003] Compared to existing AlInGaP-based red LEDs, InGaN-based red LEDs have better mechanical stability and shorter hole diffusion lengths. Due to sidewall passivation or chemical treatment, GaN-based LEDs can maintain peak EQE and are compatible with InGaN-based green and blue Micro LEDs. InGaN-based red Micro LEDs also have lower manufacturing costs, can be scaled to larger 200mm or 300mm wafers, and have better heat / cold coefficients, making them extremely attractive. However, when the emission wavelength of InGaN-based LEDs extends to longer wavelengths, their efficiency degrades significantly, which remains a challenge for InGaN-based red LEDs.

[0004] To achieve red emission, the indium content in InGaN / GaN multiple quantum wells (MQWs) should be above 40%. Growing high-In-content InGaN QWs typically requires lower growth temperatures. Under these conditions, NH3 is difficult to dissociate, reducing atomic mobility, leading to insufficient active N sources and an increase in point defects. Furthermore, as the In content increases, the lattice and thermal mismatch between the InGaN / GaN QW barriers increases, generating a strong polarization electric field in the InGaN quantum well (QW) region, resulting in a strong quantum-confined Stark effect. For high-In-content orange-red LEDs, the polarization electric field in the InGaN QW region can reach as high as 3 to 6 MV / cm. Research has shown that the large polarization electric field causes band tilting in the orange-red InGaN QW region, resulting in reduced electron-hole wavefunction overlap, lowered radiative recombination rate, and decreased internal quantum efficiency (IQE). The polarization electric field also causes band bending in the InGaN / GaN QW barriers, hindering electron and hole injection, leading to uneven distribution of electrons and holes across different QW regions and further reducing the internal quantum efficiency (IQE). High-temperature p-type GaN must be grown on top of the high-In content red light active region. During this growth process, the quantum well active region undergoes thermal annealing, causing disordered diffusion of the In component from the active region into the barrier layer, reducing the crystal quality of the active region and, in turn, affecting the electron-hole recombination efficiency in the active region. Although various methods have been employed to improve the quantum efficiency of InGaN-based red light LEDs, the reported quantum efficiency of InGaN-based red light LEDs remains very low and cannot meet application requirements. Summary of the Invention

[0005] The present invention aims to provide a gallium nitride-based red light-emitting diode epitaxial structure, its preparation, and application, addressing the low quantum efficiency of existing InGaN-based red LEDs. A composite protective layer with a stress-relieving effect is grown between the high-indium (In) red light active region and the high-temperature p-type layer. This composite protective layer reduces the compressive stress on the red light quantum wells in the active region near the p-type layer, while also minimizing thermal damage to the quantum wells caused by thermal annealing during the growth of the high-temperature p-type layer.

[0006] In order to achieve the above object, the present invention provides a gallium nitride-based red light emitting diode epitaxial structure, which comprises, from bottom to top, the following:

[0007] Sapphire substrate, low-temperature GaN nucleation layer, high-temperature undoped GaN buffer layer, n-type GaN layer, low-temperature GaN V-type layer, In x1 Ga 1-x1 N / GaN stress relief layer, In x Ga 1-x N / In y Ga 1-y N multi-quantum well light-emitting layer structure MQW, composite protective layer, p-type Aly1 Ga -y1 N electron blocking layer, high temperature p-type GaN layer and p-type InGaN contact layer; the In x Ga 1-x N / In y Ga 1-y The x in N is 0.35 to 0.5; y is 0 to 0.1 and is not 0; the p-type Al y1 Ga -y1 The y1 in N is 0.01 to 0.30; the composite protective layer is composed of In x1 Ga 1-x1 N single layer and GaN single layer composition, In x1 Ga 1-x1 N monolayer and Al y2 In x2 Ga 1-x2-y2 N single layer composition, In x1 Ga 1-x1 N / GaN superlattice structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition or In x1 Ga 1-x1 N / GaN quantum well structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition; the In x1 Ga 1-x1 x1 in N is 0.01 to 0.39; y2 In x2 Ga 1-x2-y2 In N, x2 is 0.01 to 0.10, and y2 is 0.01 to 0.20.

[0008] Preferably, in the composite protective layer, the In x1 Ga 1-x1 The thickness of the N single layer is 10-300 nm, and the thickness of the GaN single layer is 1-300 nm.

[0009] More preferably, the In x1 Ga 1-x1 The thickness of the N single layer is 50 nm, and the thickness of the GaN single layer is 80 nm.

[0010] More preferably, the In x1 Ga 1-x1 x1 in N is 0.05.

[0011] Preferably, in the composite protective layer, the In x1 Ga 1-x1 The thickness of the N single layer is 10 to 300 nm, and the Aly2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

[0012] Preferably, in the composite protective layer above the active area, the In x1 Ga 1-x1 The period number of the N / GaN superlattice structure is 1 to 50, the thickness of the well layer is 1 to 10 nm, the thickness of the barrier layer is 1 to 5 nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

[0013] More preferably, the In x1 Ga 1-x1 The period number of the N / GaN superlattice structure is 5, the well layer thickness is 3nm, the barrier layer thickness is 5nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N monolayer is 80 nm.

[0014] More preferably, the In x1 Ga 1-x1 The x1 in the N / GaN superlattice structure is 0.05, and the Al y2 In x2 Ga 1-x2-y2 In the N single layer, x2 is 0.05 and y2 is 0.10.

[0015] Preferably, in the composite protective layer, the In x1 Ga 1-x1 The period number of the N / GaN quantum well structure is 1 to 50, the well layer thickness is 1 to 10 nm, the barrier layer thickness is 5 to 30 nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

[0016] More preferably, the In x1 Ga 1-x1 The period number of the N / GaN quantum well structure is 2, the well layer thickness is 2nm, the barrier layer thickness is 10nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N monolayer is 80 nm.

[0017] The present invention provides a method for preparing a gallium nitride-based red light-emitting diode epitaxial structure as described above, the method comprising:

[0018] (1) The sapphire substrate was treated in a hydrogen atmosphere at a temperature of 1080°C and a reaction chamber pressure of 100 Torr, and ammonia and trimethylgallium were introduced into a hydrogen atmosphere at a temperature of 525°C and a reaction chamber pressure of 450 Torr to grow a low-temperature GaN nucleation layer in three dimensions;

[0019] (2) In a hydrogen atmosphere at a temperature of 1050°C and a reaction chamber pressure of 250 torr, ammonia and trimethyl gallium are introduced to grow a high-temperature non-doped GaN buffer layer; in a hydrogen atmosphere at a temperature of 1050°C and a reaction chamber pressure of 150 torr, trimethyl gallium, silane and ammonia are introduced to grow an n-type GaN layer;

[0020] (3) In a nitrogen atmosphere at a temperature of 800°C and a reaction chamber pressure of 300 torr, trimethyl gallium, silane, and ammonia are introduced to grow a low-temperature GaN V-type layer and grow In x1 Ga 1-x1 N / GaN stress release layer, in which when growing In x1 Ga 1-x1 When N is grown, trimethylindium, trimethylgallium and ammonia are introduced. When growing GaN, ammonia and trimethylgallium are introduced. In a nitrogen atmosphere with a temperature of 700°C and a reaction chamber pressure of 300 torr, trimethylindium, trimethylgallium and ammonia are introduced to grow In x Ga 1-x N / In y Ga 1-y N multi-quantum well light-emitting layer structure MQW;

[0021] (4) On the multi-quantum well light-emitting layer structure MQW, a composite protective layer was grown in a nitrogen atmosphere at a temperature of 830°C and a reaction chamber pressure of 300 torr; at 940°C, bismuth magnesium, trimethylaluminum, trimethylgallium and ammonia were introduced to grow p-type Al y1 Ga -y1 N electron blocking layer;

[0022] The composite protective layer is made of In x1 Ga 1-x1 N single layer and GaN single layer composition, In x1 Ga 1-x1 N monolayer and Al y2 In x2 Ga 1-x2-y2 N single layer composition, In x1 Ga 1-x1 N / GaN superlattice structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition or In x1 Ga 1-x1 N / GaN quantum well structure and Al y2 Inx2 Ga 1-x2-y2 N single layer composition;

[0023] When growing the x1 Ga 1-x1 When the N monolayer is formed, trimethyl indium, trimethyl gallium and ammonia are introduced; when the Al y2 In x2 Ga 1-x2-y2 When the N single layer is grown, cyclopentadienyl magnesium, trimethylaluminum, trimethylindium, trimethylgallium and ammonia are introduced; when the GaN single layer is grown, ammonia and trimethylgallium are introduced;

[0024] (5) In a hydrogen atmosphere at a temperature of 940°C and a reaction chamber pressure of 100 torr, cyclopentadienyl magnesium, trimethyl gallium and ammonia are introduced to grow a high-temperature p-type GaN layer; in a nitrogen atmosphere at a temperature of 700°C and a reaction chamber pressure of 300 torr, cyclopentadienyl magnesium, trimethyl indium, trimethyl gallium and ammonia are introduced to grow a p-type InGaN contact layer.

[0025] The present invention provides an application of the gallium nitride-based red light emitting diode epitaxial structure in the field of semiconductor optoelectronic technology.

[0026] The gallium nitride-based red light-emitting diode epitaxial structure of the present invention, its preparation and application, solve the problem of low quantum efficiency of existing InGaN-based red light-emitting diodes, and have the following advantages:

[0027] 1. The present invention grows a composite protective layer with a stress-releasing effect between the high-indium (In) red light active region and the high-temperature p-type layer. The composite protective layer reduces the compressive stress on the red light quantum well on the side of the active region close to the p-type layer, and at the same time reduces the thermal damage caused by thermal annealing of the high-temperature p-type layer to the quantum well during the growth process.

[0028] 2. Compared to LED samples without a composite protective layer, the GaN-based red LEDs with a stress-relieving composite protective layer exhibited significantly improved internal quantum efficiency, reaching up to 110%. The parameter ranges of the present invention were achieved through extensive creative effort; red LEDs fabricated outside these parameters exhibit relatively poor photoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a vertical cross-sectional view of the gallium nitride-based red light emitting diode in Example 1 of the present invention.

[0030] Figure 2 It is a vertical cross-sectional view of the gallium nitride-based red light emitting diode in Example 2 of the present invention.

[0031] Figure 3It is a vertical cross-sectional view of the gallium nitride-based red light emitting diode in comparative example 1 of the present invention.

[0032] Figure 4 This is a comparison chart of the internal quantum efficiency test results of the gallium nitride-based red light emitting diodes of Comparative Example 1, Example 1 and Example 2. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0034] Example 1

[0035] A gallium nitride-based red light emitting diode epitaxial structure, the structure is as follows:

[0036] like Figure 1 As shown in FIG, a vertical cross-sectional view of a gallium nitride-based red light emitting diode in Example 1 of the present invention. Figure 1 It can be seen that the vertical cross-section of the gallium nitride-based red light-emitting diode in Example 1 of the present invention includes an LED epitaxial structure, which is sequentially as follows from bottom to top: sapphire substrate 101, low-temperature GaN nucleation layer 102, high-temperature undoped GaN buffer layer 103, n-type GaN layer 104, low-temperature GaN V-type layer 105, In 0.1 Ga 0.9 N / GaN stress relief layer 106, In 0.4 Ga 0.6 N / GaN multi-quantum well light-emitting layer structure MQW107, InGaN protective layer 108, GaN protective layer 109, p-type Al 0.15 Ga 0.85 N electron blocking layer 110 , high temperature p-type GaN layer 111 and p-type InGaN contact layer 112 .

[0037] The above-mentioned method for preparing the epitaxial structure of the gallium nitride-based red light-emitting diode uses an Aixtron tightly coupled vertical reaction chamber MOCVD growth system. During the growth process, trimethyl gallium (TMGa), trimethyl indium (TMIn) and trimethyl aluminum (TMAl) are used as group III sources, ammonia (NH3) is used as a group V source, silane (SiH4) is used as an n-type dopant source, and bis(cyclopentadienyl) magnesium (Cp2Mg) is used as a p-type dopant source. The method specifically includes:

[0038] (1) First, a 450 μm thick two-inch sapphire substrate 101 is treated in a metal organic compound vapor phase epitaxy reaction chamber at a temperature of 1080° C. and a reaction chamber pressure of 100 torr in a hydrogen atmosphere for 15 minutes. Then, the temperature is lowered to 525° C. and a reaction chamber pressure of 450 torr in a hydrogen (H2) atmosphere. Gaseous ammonia (NH3) and trimethylgallium (TMGa) (V / III molar ratio (the molar ratio of group V elements to group III elements) is (1000-20000) : 1) are simultaneously introduced into the reaction chamber to grow a 30 nm thick low-temperature GaN nucleation layer 102.

[0039] (2) At 1050°C and a reaction chamber pressure of 250 torr in a hydrogen (H2) atmosphere, ammonia (NH3) and trimethyl gallium (TMGa) in a molar ratio of (1000-20000) : 1 were introduced into the reaction chamber simultaneously to grow a 1.5 μm thick high-temperature non-doped GaN buffer layer 103; at 1050°C and a reaction chamber pressure of 150 torr in a hydrogen (H2) atmosphere, trimethyl gallium (TMGa), silane (SiH4) and ammonia (NH3) were introduced into the reaction chamber simultaneously to grow a 4 μm thick n-type GaN layer 104, wherein the Si doping concentration was 5×10 18 cm -3 (indicates the number of atoms), the molar ratio of ammonia (NH3) and trimethylgallium (TMGa) is (1000-10000):1;

[0040] (3) At 800°C and a nitrogen (N2) atmosphere with a reaction chamber pressure of 300 torr, gaseous trimethyl gallium (TMGa), silane (SiH4) and ammonia (NH3) are simultaneously introduced into the reaction chamber to grow a 250 nm thick low-temperature GaN V-type layer 105, wherein the Si doping concentration is 1×10 17 cm -3 , the molar ratio of ammonia (NH3) and trimethyl gallium (TMGa) is (1000-10000):1; then 20 cycles of In 0.1 Ga 0.9 N / GaN superlattice (stress relief layer 106), where In 0.1 Ga 0.9 The thickness of the N well layer is 3nm, and the thickness of the GaN barrier layer is 3nm. 0.1 Ga 0.9When N is added, gaseous trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) are introduced, the molar ratio of trimethylindium (TMIn) and trimethylgallium (TMGa) is 1:9, and the amount of ammonia (NH3) and the amount of trimethylindium (TMIn) and trimethylgallium (TMGa) are in a ratio of (5000-20000):1 (the V / III molar ratio is (5000-20000):1); when growing GaN, gaseous ammonia (NH3) and trimethylgallium (TMGa) are introduced in a molar ratio of (1000-10000):1; under a nitrogen (N2) atmosphere at 700°C and a reaction chamber pressure of 300torr, the V / III molar ratio is (5000-20000):1, and then 3 cycles of In are grown. 0.4 Ga 0.6 N / GaN multi-quantum well light-emitting layer structure MQW107 (multi-quantum well active region), where In 0.4 Ga 0.6 The thickness of the N quantum well layer is 2.5nm, and the thickness of the GaN barrier layer is 5nm. 0.4 Ga 0.6 When growing N / GaN, gaseous trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) are introduced, the molar ratio of trimethylindium (TMIn) to trimethylgallium (TMGa) is 4:6, and the sum of the amount of ammonia (NH3) and the amount of trimethylindium (TMIn) and trimethylgallium (TMGa) is (5000-20000):1 (the V / III molar ratio is (5000-20000):1); when growing GaN, gaseous ammonia (NH3) and trimethylgallium (TMGa) are introduced at a molar ratio of (1000-10000):1;

[0041] (4) A composite protective layer with stress release function was grown on the multi-quantum well active region at 830°C in a nitrogen atmosphere with a reaction chamber pressure of 300 torr, with a V / III molar ratio of (5000-20000):1; the composite protective layer consisted of 50 nm In 0.05 Ga 0.95 N protective layer 108 and low temperature 80nm GaN protective layer 109, wherein when the In 0.05 Ga 0.95When the temperature is 400°C, gaseous trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) are introduced, the molar ratio of trimethylindium (TMIn) and trimethylgallium (TMGa) is 5:95, and the amount of ammonia (NH3) and the amount of trimethylindium (TMIn) and trimethylgallium (TMGa) are (5000-20000):1 (the V / III molar ratio is (5000-20000):1); when growing GaN, gaseous ammonia (NH3) and trimethylgallium (TMGa) are introduced at a molar ratio of (1000-10000):1; at 940°C, gaseous bismuth magnesium (Cp2Mg), trimethylaluminum (TMAl), trimethylgallium (TMGa) and ammonia (NH3) are introduced to grow p-type Al 0.15 Ga 0.85 N electron blocking layer 110, wherein the thickness of the electron blocking layer 110 is 20 nm, and the Mg doping concentration is 5×10 17 cm -3 The molar ratio of trimethylaluminum (TMAl) and trimethylgallium (TMGa) is 15:85, and the molar ratio of ammonia (NH3) to the molar ratio of trimethylaluminum (TMAl) and trimethylgallium (TMGa) is (5000-20000):1.

[0042] (5) Under a hydrogen atmosphere at 940°C and a reaction chamber pressure of 100 torr, a 100 nm high-temperature p-type GaN layer 111 was grown by introducing gaseous cyclopentadienyl magnesium (Cp2Mg), trimethyl gallium (TMGa) and ammonia (NH3), wherein the Mg doping concentration was 5×10 17 cm -3 The molar ratio of ammonia (NH3) and trimethylgallium (TMGa) is (5000-20000) : 1; at 700 ° C, in a nitrogen atmosphere with a reaction chamber pressure of 300 torr, gaseous bismuth magnesium (Cp2Mg), trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) are introduced to grow 3nm p-type In 0.05 Ga 0.95 The N contact layer 112 has a Mg doping concentration of 2×10 18 cm -3 The molar ratio of trimethylindium (TMIn) and trimethylgallium (TMGa) is 5:95, and the molar ratio of ammonia (NH3) to the molar ratio of trimethylindium (TMIn) and trimethylgallium (TMGa) is (5000-20000):1.

[0043] Example 2

[0044] A gallium nitride-based red light emitting diode epitaxial structure is substantially the same as that of embodiment 1, such as Figure 2As shown, the vertical cross-sectional view of the gallium nitride-based red light emitting diode in Example 2 of the present invention is shown. Figure 2 It can be seen that the difference from Example 1 is that the InGaN protective layer 108 and the GaN protective layer 109 are adjusted to 5 periods (the well layer thickness is 3 nm). 0.05 Ga 0.95 N / GaN superlattice protection layer 108 and 80nmAl 0.1 In 0.05 Ga 0.85 N protective layer 109 .

[0045] The method for preparing the above-mentioned GaN-based red light emitting diode epitaxial structure is basically the same as that in Example 1, except that:

[0046] In step (4), the composite protective layer is composed of 5 periods (3nm)In 0.05 Ga 0.95 N / (barrier layer thickness is 5nm)GaN superlattice protection layer 108 and 80nm Al 0.1 In 0.05 Ga 0.85 N protective layer 109 is composed of In 0.05 Ga 0.95 When N is grown, gaseous trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) are introduced, the molar ratio of trimethylindium (TMIn) and trimethylgallium (TMGa) is 5:95, and the amount of ammonia (NH3) and the sum of the amount of trimethylindium (TMIn) and trimethylgallium (TMGa) are (5000-20000):1; when growing GaN, gaseous ammonia (NH3) and trimethylgallium (TMGa) are introduced with a molar ratio of (1000-10000):1; when growing Al 0.1 In 0.05 Ga 0.85 N, gaseous bismuth magnesium (Cp2Mg), trimethylaluminum (TMAl), trimethylindium (TMIn), trimethylgallium (TMGa) and ammonia (NH3) were introduced, and the Mg doping concentration was 2×10 18 cm -3 The molar ratio of trimethylaluminum (TMAl), trimethylindium (TMIn) and trimethylgallium (TMGa) is 10:5:85, and the molar ratio of ammonia (NH3) to the molar ratio of trimethylaluminum (TMAl), trimethylindium (TMIn) and trimethylgallium (TMGa) is (5000-20000):1.

[0047] Comparative Example 1

[0048] A gallium nitride-based red light emitting diode epitaxial structure without a composite protective layer is basically the same as that of Example 1, such as Figure 3 As shown in FIG, a vertical cross-sectional view of a gallium nitride-based red light emitting diode in comparative example 1 of the present invention. Figure 3 It can be seen that the difference from Example 1 is that there is no In 0.05 Ga 0.95 N protective layer 108 .

[0049] The method for preparing the above-mentioned GaN-based red light emitting diode epitaxial structure is basically the same as that in Example 1, except that:

[0050] In step (2), the Si doping concentration is increased from 5×10 18 cm -3 Adjusted to 6×10 18 cm -3 ;

[0051] In step (3), 3 cycles of In are grown at 700°C and a nitrogen (N2) atmosphere with a reaction chamber pressure of 350 torr. 0.4 Ga 0.6 N / GaN multi-quantum well light-emitting layer structure MQW107 (multi-quantum well active region), where In 0.4 Ga 0.6 The thickness of the N quantum well layer is 2.5nm, and the thickness of the GaN barrier layer is 10nm;

[0052] In step (4), there is no In 0.05 Ga 0.95 N protective layer 108, on the multi-quantum well active region, in a nitrogen atmosphere or nitrogen-hydrogen mixed atmosphere at 800°C and a reaction chamber pressure of 300 torr, grow an 80nm low-temperature GaN protective layer 109; at 940°C, grow a p-type Al 0.15 Ga 0.85 N electron blocking layer 110, wherein the electron blocking layer thickness is 18nm, and the Mg doping concentration is 2×10 17 cm -3 .

[0053] In step (5), a 150 nm high temperature p-type GaN layer 112 is grown in a hydrogen atmosphere at 940°C and a reaction chamber pressure of 100 torr, wherein the Mg doping concentration is 5×10 17 cm -3 .

[0054] Experimental Example 1 Testing the Internal Quantum Efficiency of Red Light Emitting Diode Epitaxial Wafers of Example 1, Example 2 and Comparative Example 1

[0055] After the epitaxial growth of the red light-emitting diodes in Example 1, Example 2, and Comparative Example 1 was completed, the reaction chamber temperature was lowered to 750°C, and annealing treatment was performed in a pure nitrogen atmosphere for 5-20 minutes. The temperature was then lowered to room temperature to terminate the growth, resulting in the LED samples of Example 1, Example 2, and Comparative Example 1. The internal quantum efficiency of the red light-emitting diode epitaxial wafer LED samples in Example 1, Example 2, and Comparative Example 1 was tested using variable-temperature photoluminescence (PL). The internal quantum efficiency of the red LED epitaxial wafers was tested using variable-temperature PL, and the ratio of the PL integrated intensity at 300K to the PL integrated intensity at 5K was used to obtain the internal quantum efficiency of the epitaxial wafers.

[0056] like Figure 4 As shown in FIG, the comparison chart of the internal quantum efficiency test results of the gallium nitride-based red light emitting diodes of comparative example 1, embodiment 1 and embodiment 2. Figure 4 It can be seen that the internal quantum efficiency of the gallium nitride-based red light-emitting diode without a composite protective layer in Comparative Example 1 is the lowest. Compared with the LED sample without a composite protective layer in Comparative Example 1, the internal quantum efficiency of the gallium nitride-based red light-emitting diodes with a composite protective layer with stress relief function in Examples 1 and 2 is significantly improved, with the LED sample in Example 1 improving by 65% ​​and the LED sample in Example 2 improving by 110%.

[0057] Although the present invention has been described in detail through the above preferred embodiments, it should be understood that the above description is not intended to limit the present invention. After reading the above description, various modifications and substitutions of the present invention will become apparent to those skilled in the art. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A gallium nitride-based red light emitting diode epitaxial structure, characterized in that: The epitaxial structure includes, from bottom to top: Sapphire substrate, low-temperature GaN nucleation layer, high-temperature undoped GaN buffer layer, n-type GaN layer, low-temperature GaN V-type layer, In x1 Ga 1-x1 N / GaN stress relief layer, In x Ga 1-x N / In y Ga 1-y N multi-quantum well light-emitting layer structure MQW, composite protective layer, p-type Al y1 Ga -y1 N electron blocking layer, high temperature p-type GaN layer and p-type InGaN contact layer; In x Ga 1-x N / In y Ga 1-y In N, x is 0.35 to 0.5; y is 0 to 0.1 and is not 0; The p-type Al y1 Ga -y1 y1 in N is 0.01 to 0.30; The composite protective layer is composed of In x1 Ga 1-x1 N single layer and GaN single layer composition, In x1 Ga 1-x1 N monolayer and Al y2 In x2 Ga 1-x2-y2 N single layer composition, In x1 Ga 1-x1 N / GaN superlattice structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition or In x1 Ga 1-x1 N / GaN quantum well structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition; In x1 Ga 1-x1 x1 in N is 0.01 to 0.39; The Al y2 In x2 Ga 1-x2-y2 In N, x2 is 0.01 to 0.10, and y2 is 0.01 to 0.

20.

2. The gallium nitride-based red light emitting diode epitaxial structure according to claim 1, characterized in that: In the composite protective layer, the In x1 Ga 1-x1 The thickness of the N single layer is 10-300 nm, and the thickness of the GaN single layer is 1-300 nm.

3. The gallium nitride-based red light emitting diode epitaxial structure according to claim 2, characterized in that: In x1 Ga 1-x1 The thickness of the N single layer is 50 nm, the thickness of the GaN single layer is 80 nm, and the thickness of the In x1 Ga 1-x1 The x1 in N is 0.

05.

4. The gallium nitride-based red light emitting diode epitaxial structure according to claim 1, characterized in that: In the composite protective layer, the In x1 Ga 1-x1 The thickness of the N single layer is 10 to 300 nm. y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

5. The gallium nitride-based red light emitting diode epitaxial structure according to claim 1, characterized in that: In the composite protective layer above the active area, the In x1 Ga 1-x1 The period number of the N / GaN superlattice structure is 1 to 50, the thickness of the well layer is 1 to 10 nm, the thickness of the barrier layer is 1 to 5 nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

6. The gallium nitride-based red light emitting diode epitaxial structure according to claim 5, characterized in that: In x1 Ga 1-x1 The period number of the N / GaN superlattice structure is 5, the well layer thickness is 3nm, the barrier layer thickness is 5nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 80 nm. x1 Ga 1-x1 The x1 in the N / GaN superlattice structure is 0.

05. y2 In x2 Ga 1-x2-y2 In the N single layer, x2 is 0.05 and y2 is 0.

10.

7. The gallium nitride-based red light emitting diode epitaxial structure according to claim 1, characterized in that: In the composite protective layer, the In x1 Ga 1-x1 The period number of the N / GaN quantum well structure is 1 to 50, the thickness of the well layer is 1 to 10 nm, the thickness of the barrier layer is 5 to 30 nm, and the Al y2 In x2 Ga 1-x2-y2 The thickness of the N single layer is 1 to 300 nm.

8. A method for preparing a gallium nitride-based red light emitting diode epitaxial structure as claimed in any one of claims 1 to 7, characterized in that: The method includes: (1) treating a sapphire substrate in a hydrogen atmosphere at a temperature of 1080° C. and a reaction chamber pressure of 100 torr, and introducing ammonia and trimethylgallium into a hydrogen atmosphere at a temperature of 525° C. and a reaction chamber pressure of 450 torr to grow a low-temperature GaN nucleation layer in three dimensions; (2) In a hydrogen atmosphere at a temperature of 1050° C. and a reaction chamber pressure of 250 torr, ammonia and trimethylgallium were introduced to grow a high-temperature non-doped GaN buffer layer; in a hydrogen atmosphere at a temperature of 1050° C. and a reaction chamber pressure of 150 torr, trimethylgallium, silane and ammonia were introduced to grow an n-type GaN layer; (3) In a nitrogen atmosphere at a temperature of 800°C and a pressure of 300 torr, trimethylgallium, silane, and ammonia are introduced to grow a low-temperature GaN V-type layer and In x1 Ga 1-x1 N / GaN stress release layer, in which when In is grown x1 Ga 1-x1 When N is grown, trimethylindium, trimethylgallium and ammonia are introduced. When GaN is grown, ammonia and trimethylgallium are introduced. When In is grown, trimethylindium, trimethylgallium and ammonia are introduced at a temperature of 700°C and a reaction chamber pressure of 300 torr. x Ga 1-x N / In y Ga 1-y N multiple quantum well light emitting layer structure MQW; (4) On the multi-quantum well light-emitting layer structure MQW, a composite protective layer was grown in a nitrogen atmosphere at a temperature of 830°C and a reaction chamber pressure of 300 torr; at 940°C, bis(cyclopentadienyl)magnesium, trimethylaluminum, trimethylgallium and ammonia were introduced to grow p-type Al y1 Ga -y1 N electron blocking layer; The composite protective layer is composed of In x1 Ga 1-x1 N single layer and GaN single layer composition, In x1 Ga 1-x1 N monolayer and Al y2 In x2 Ga 1-x2-y2 N single layer composition, In x1 Ga 1-x1 N / GaN superlattice structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition or In x1 Ga 1-x1 N / GaN quantum well structure and Al y2 In x2 Ga 1-x2-y2 N single layer composition; When growing the x1 Ga 1-x1 When the N single layer is formed, trimethyl indium, trimethyl gallium and ammonia are introduced; when the Al y2 In x2 Ga 1-x2-y2 When the N single layer is formed, bismuthocene magnesium, trimethylaluminum, trimethylindium, trimethylgallium and ammonia are introduced; when the GaN single layer is formed, ammonia and trimethylgallium are introduced; (5) In a hydrogen atmosphere at a temperature of 940°C and a reaction chamber pressure of 100 torr, cyclopentadienyl magnesium, trimethyl gallium and ammonia are introduced to grow a high-temperature p-type GaN layer; in a nitrogen atmosphere at a temperature of 700°C and a reaction chamber pressure of 300 torr, cyclopentadienyl magnesium, trimethyl indium, trimethyl gallium and ammonia are introduced to grow a p-type InGaN contact layer.

9. The preparation method according to claim 8, characterized in that: The trimethylgallium, trimethylindium and trimethylaluminum are used as group III sources, ammonia is used as a group V source, silane is used as an n-type doping source, and bismuth magnesium (Cp2Mg) is used as a p-type doping source. The molar ratio of the elements of the group V source to the elements of the group III source is (1000-20000):

1.

10. Application of the gallium nitride-based red light emitting diode epitaxial structure as claimed in any one of claims 1 to 7 in the field of semiconductor optoelectronic technology.